Rescue of Non-Performing Credit in Post Pandemi Covid-19 Village Credit Institutions in the Adat Ped Village, Nusa Penida District, Klungkung Regency - I Nyoman Sujana; Putu Ayu Sriasih Wesna; I wayan Kartika Jaya Utama (Fakultas Hukum, Universitas Warmadewa, 2023)
The tourism business is the mainstay of the Small Island of Nusa Penida as an inseparable part of the Island of the Gods, Bali. The existence of the COVID-19 Pandemic has made Bali tourism and is no exception also an impact on the tourism business in Nusa Penida. The people's economy in Nusa Penida experienced very severe shocks and even eroded almost all economic sectors; including the impact on the financial services sector owned by a traditional village called The village credit institution (The Village Credit Institution). The aim research is to know how are the efforts to save problem loans carried out by the Management of The Village Credit Institution Desa Adat Ped in the post-Covid-19 pandemic era. This legal issue will be studied using a normative legal approach complemented by a sociological approach carried out by The Village Credit INSTITUTION administrators throughout the Nusa Penida sub-district, Klungkung regency - Bali. Normative legal theory is concerned with the ends and justifications for the law as a whole and for particular legal rules. The result shows that Through Restructuring, namely efforts in the form of changing the terms of the credit agreement or converting all or part of the credit into company equity, which is carried out with or without Rescheduling and/or reconditioning.